1997
DOI: 10.1111/j.1600-0722.1997.tb00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary levels of immunoglobulin A in Triathletes

Abstract: We investigated whether the physical exercise of an olympic distance triathlon affected the salivary IgA excretion of triathletes, as a biomarker for mucosal immune defence. 42 triathletes participated in the study. It was found that the salivary flow rate was decreased significantly after the race, thereby resulting in a significant reduction of the total salivary IgA output. The salivary IgA concentration (mg IgA/ml) did not differ, but expressed as total salivary protein, a significant reduction was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
74
3
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 24 publications
13
74
3
6
Order By: Relevance
“…Salivary IgA has been classically recognized as one of major effectors in host resistance to many pathogens in oral cavity, and many studies investigated the impact of transient or repeated exercise on its salivary levels 39,40) . Decreases in salivary However, the precise mechanism by which the levels of salivary inflammatory cytokines were increased after acute prolonged strenuous exercise.…”
Section: ⅳ.Discussionmentioning
confidence: 99%
“…Salivary IgA has been classically recognized as one of major effectors in host resistance to many pathogens in oral cavity, and many studies investigated the impact of transient or repeated exercise on its salivary levels 39,40) . Decreases in salivary However, the precise mechanism by which the levels of salivary inflammatory cytokines were increased after acute prolonged strenuous exercise.…”
Section: ⅳ.Discussionmentioning
confidence: 99%
“…2). A decrease in absolute concentrations of salivary IgA has been reported for elite skiers, 43 swimmers, 4,5 distance runners 44 and cyclists. 11,13 In squash players, the response of 13 8 Male cyclists Decreased absolute concentrations Mackinnon et al (1989) 11 Decreased as a proportion of total protein after a 2 h exhaustive cycle ergometer test Schouten et al (1988) 49 175 Young adults Decreased after maximal treadmill test in females, increased after maximal treadmill test in males Tharp and Barnes (1990) 4 21 Swimmers Decreased after routine training session Cameron and Priddle (1990) 44 13 Distance runners Decreased after 10.5 km high-intensity run Mackinnon et al (1992) 20 12 Female hockey players Decreased proportion relative to total protein after each training session and competition 7 29 Young males Decreased after maximal treadmill running 48 24 Young males Decreased after submaximal treadmill running 46 8 Male kayakers Decreased secretion rate after each training session Mackinnon and Jenkins (1993) 47 12 Young males Decreased output after brief supramaximal interval cycling Mackinnon and Hooper (1994) 23 10 Joggers Decreased after moderate treadmill exercise 8 Distance runners 5 26 Swimmers Decreased after routine training sessions in swimmers 12 Controls…”
Section: Salivary Igamentioning
confidence: 90%
“…No change after routine exercise in controls Steerenberg et al (1997) 43 42 Triathletes Decreased output after race 58 22 Swimmers Decreased after routine training sessions 12 Elite kayaker (case study) Decreased after each training session Nehlsen-Cannarella et al (2000) 45 20 Women rowers Decreased after 2 h training session salivary IgA to exercise is characterized by an increased concentration in healthy athletes, but a decrease in those who subsequently develop an URTI. 20 A recent study of elite women rowers has reported that salivary IgA concentration decreases by almost 50% after 2 h of rowing training.…”
Section: Salivary Igamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, periods of intense, frequent, endurance--based training have consistently been associated with self--reported symptoms of URTI in elite--level athletes (Gleeson 2000;Gleeson and Pyne 2000;Nieman 2000). Low levels of salivary secretory Immunoglubulin A (SIgA) have been linked with an increased risk of URTI (Fahlman and Engels 2005;Gleeson et al 2012;Hanson et al 1983;Neville et al 2008) and prolonged, high--intensity exercise bouts lower both the concentration and secretion of salivary SIgA (Fahlman et al 2001;Nieman et al 2006;Steerenberg et al 1997;Tomasi et al 1982;Usui et al 2011). On the other hand, shorter exercise bouts, or low to moderate--intensity exercise, may actually increase salivary SIgA concentration and secretion (Allgrove et al 2008;Li and Gleeson 2004), indicating that mucosal immune integrity, and indeed URTI risk, is dependent on the duration and intensity of the exercise performed.…”
Section: Introductionmentioning
confidence: 99%